2008
DOI: 10.1021/ac800294f
|View full text |Cite
|
Sign up to set email alerts
|

Living Cells of Staphylococcus aureus Immobilized onto the Capillary Surface in Electrochromatography: A Tool for Screening of Biofilms

Abstract: Microorganisms attach to nonliving surfaces in many natural, industrial, and medical environments, enveloped within extracellular polymeric substances. The result is a biofilm. Biofilms are reported to exist in 65-80% of bacterial infections refractory to host defenses and antibiotics therapy and are regarded as a central problem in present-day medical microbiology. Understanding of the parameters governing the interaction of antimicrobials with biofilms is thus of great interest in any attempt to increase bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Biofilm has been found in 65-80% of the bacterial infections, and is considered refractory to host defenses in antibiotic therapy [1]. Among the biofilm forming bacteria, Staphylococcus aureus is responsible for severe skin infections to such major diseases as bacteremia, endocarditis and osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm has been found in 65-80% of the bacterial infections, and is considered refractory to host defenses in antibiotic therapy [1]. Among the biofilm forming bacteria, Staphylococcus aureus is responsible for severe skin infections to such major diseases as bacteremia, endocarditis and osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%
“…The retention of analytes is due to a combination of electrophoretic migration and chromatographic retention. Some authors have shown that CEC technique is successful applied to the separation, identification, and characterization of mixtures of both living and dead bacteria contained in biofilm structure, very useful in biofilm metabolomics research [46].…”
Section: Microfluidicsmentioning
confidence: 99%
“…Biofilm, an extracellular polymeric matrix secreted by certain microorganisms, has been found in 65%–80% of bacterial infections, and is considered refractory to host defenses in antibiotic therapy [ 1 ]. Among the biofilm-forming bacteria, Staphylococcus aureus is responsible for health problems ranging from minor skin infections to such major diseases as bacteremia, endocarditis and osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%